Insomnia drug therapy in COVID-19 patients; a Letter to Editor - Ali Rismanbaf (Babol University of Medical Sciences, 2020)
Coronavirus disease 2019 (COVID-19) is a highly contagious disease caused by the newly emerging SARS-CoV-2 virus that was first reported in December 2019 and was announced as a pandemic disease on March 11th, according to a World Health Organization (WHO) warning (1). SARS-CoV-2 is mainly transmitted through respiratory droplets and close contact, accordingly, requires treatment in isolation. It has been reported that many patients developed sleep disturbances due to isolation treatment or medication use, which can lead to pathological events and impaired immunity, and need to prescribe hypnotic medications (2). Also, some patients may have taken hypnotic medications before developing COVID-19 and may be dependent on these medications, and now, with the onset of COVID-19 and the addition of new drugs for its treatment, they need to change their hypnotic medications.